Minat dan Bakat Mahasiswa Dakwah Pada Kegiatan Khithabah - Jujun Junaedi (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2012)
Khithabah as part of sermons, including one method of propagation in the context of mass communication that preachers often do. Khithabah become a popular paradigm that the escort mission dynamics of mass media propaganda with all kedakwahannya effectiveness. Often khithabah conducted limited spread Islamic ideology which incidentally is the transfer of ideas with a bunch of speeches recreational bandage which in turn offers the essence of propaganda about itself. However, the insertions are not rare in any recreational activity khithabah a bargaining power for their own propaganda and a lover of excellence in the Islamic world that in fact describe the nature of grace for the whole of nature.